Wasathiyyah in the Hadith: Normative Foundations, Prophetic Practice, and Post-Prophetic Challenges - Gusnanda Gusnanda; Sri Chalida; Awis Karni; Ade Irwansyah (Jurnal Ulunnuha, 2026)
This article examines the tension between the normative ideals of wasathiyyah (moderation) ‎articulated in the hadith tradition and their historical implementation in early Islam. While ‎previous studies have primarily focused on the theological and ethical dimensions of Islamic ‎moderation, limited attention has been given to the relationship between normative hadith ‎teachings and the political realities that emerged after the Prophet Muhammad’s death. ‎Employing a thematic hadith analysis combined with a historical-critical approach, this study ‎analyzes selected hadiths on moderation, balance, anti-extremism (ghuluw), and the ‎fulfillment of rights, alongside historical sources concerning the Medina Charter and early ‎Islamic political developments. The findings demonstrate that the hadith tradition ‎consistently promotes moderation as an ethical framework grounded in justice, balance, and ‎proportionality. These principles were institutionally embodied in the Prophet’s leadership, ‎particularly through the Medina Charter, which provided a model for managing religious ‎and social diversity. However, the study finds that post-Prophetic political conflicts, ‎succession disputes, and sectarian contestations complicated the realization of these ideals, ‎transforming wasathiyyah from a lived political ethic into a contested moral aspiration. ‎Theoretically, this study argues that wasathiyyah should be understood not merely as a ‎theological doctrine but as a dynamic ethical framework whose implementation is shaped by ‎historical and political contexts. By integrating normative hadith analysis with historical ‎inquiry, the article contributes to contemporary scholarship on Islamic moderation, ‎pluralism, and the relationship between religious ideals and political practice.‎